THE INFLUENCE OF INTELLECTUAL CAPITAL, GOOD CORPORATE GOVERNANCE AND CORPORATE SOCIAL RESPONSIBILITY ON FIRM VALUE WITH PROFITABILITY AS AN INTERVENING VARIABLE - Mutiah Nasution; Isfenti Sadalia; Nisrul Irawati (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
This study aims to determine the effect of Intellectual Capital, Good Corporate Governance and Corporate Social Responsibility on Firm Value with Profitability as an Intervening Variable. This research uses data Secondary which is the publication of the Indonesia Stock Exchange and the Malaysia Stock Exchange, reference books, journals, research results, and data on the internet related to the research topic. The data analysis method used is a statistical method assisted by the Smart PLS program. The results showed that VAIC (X1) has a positive and significant direction on the Profitability (ROA) variable both in Indonesia and Malaysia, GCG (X2) has a positive and significant direction on the Profitability (ROA) variable in Indonesia while in Malaysia it has a positive direction but not significant to the Profitability variable, CSR (X3) has a positive but not significant effect on the Profitability (ROA) variable in Indonesia and Malaysia, VAIC (X1) has a positive but not significant effect on Firm Value.